Strategi Komunikasi Lingkungan dalam Pelestarian Hutan Lindung pada Masyarakat Adat di Kenegerian Sentajo Kabupaten Kuantan Singingi - Rahmadi Rahmadi; Noor Efni Salam; Zulkarnain Zulkarnain (Universitas Riau, 2022)
Kenegerian Sentajo protected forest serves as a protector of the community and natural life support systems, regulates water systems, prevents floods, controls erosion, and maintains soil fertility. The management of forest resources by the community is quite unique because it is still communally regulated, which is closely related to the kinship system and leadership of local indigenous peoples. This encourages the formation of strong communication relationships or interactions between communities and their forest resources. However, in reality, the indigenous people of Sentajo Regency have not obeyed the customary rules, which resulted in the forest that was originally preserved has begun to be converted to function by the community. The forest, whose precedence is beautiful, has now partially turned into plantation land and building houses for residents. This study aims to 1) Analyze environmental communication planning in the preservation of the Kenegerian Sentajo protected forest in Kuantan Singingi Regency; 2) Analyze the implementation and evaluation of environmental communication in the preservation of the Kenegerian Sentajo protected forest in Kuantan Singingi Regency. This research uses qualitative methods. Data collection techniques are carried out through interviews, observations, and documentation. Informants totaled 8 (eight) purposively determined persons. The data analysis technique used in this study is carried out in several stages, namely data reduction, data presentation and drawing conclusions, and testing the validity of the data using triangulation. The results of this study show that: First, the planning stage begins with an assessment which includes analyzing the situation and identifying the problem of environmental damage that occurs, Analysis of parties or actors involved, Then, planning which includes developing communication strategies, motivating and mobilizing communities with the division of indigenous territories and the selection of media and communicators. Second, this implementation stage begins with the production stage, which includes the design of the message to be delivered. Furthermore, the implementation stage is in the form of the application of customary norms, the application of socio-cultural values, and community empowerment through tree and rattan planting, their implementation, and documentation after evaluation.